Comprehensive Dictionary of Modern Church Slavonic. Vol. II. “В” - Margarita I. Chernysheva (Slovene, 2019)
[Rev. of: Davydenkova M. E., Dobrovolsky I. S., Kaluzhnin N. V., Kornilaeva I. A., Kravetsky A. G., Miroshnichenko M. V., Nikiforova A. Yu., Orekhanova E. P., Petrova S. V., Pletnyova A. A., Sakharova A. V., Khitrov A. N., Comprehensive Dictionary of Contemporary Church Slavonic. Vol. II, Moscow, 2019, 544 pp.]